2013
DOI: 10.1021/jp401170j
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Anisotropic Morphology at the Nanoregime: Surface Bonding Motif Determines the Morphology Transformation of ZnO Nanostructures

Abstract: A quantitative relationship between bond length, crystal morphology, and particle size has been established to investigate the morphology transformation of ZnO nanostructures at the nanoregime. Surface bonding conditions dominate the anisotropic growth of ZnO nanoparticles. Critical surface bond lengths at which ZnO can respectively exhibit pyramid-, truncated pencil-, pencil-, and rod-like morphologies were quantitatively calculated under different extension/shrinkage degrees of Zn−O bond length in the lattic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 35 publications
3
40
0
1
Order By: Relevance
“…From the above analysis, it can be concluded that process parameters such as reaction solvent, Cs source, autoclave rotating and other reaction conditions play an important role in the morphology and crystal phase of Cs x WO 3 products. These observations confirm that the morphology control is strongly dependent on the reaction kinetics of the whole system, as concluded by the chemical bond theory of single crystal growth [32][33][34]. The morphology and crystal phase of Cs x WO 3 synthesized by solvothermal reaction with different process parameters are summarized in Table 1.…”
Section: Effects Of Autoclave Rotating On the Morphology And Crystal supporting
confidence: 79%
“…From the above analysis, it can be concluded that process parameters such as reaction solvent, Cs source, autoclave rotating and other reaction conditions play an important role in the morphology and crystal phase of Cs x WO 3 products. These observations confirm that the morphology control is strongly dependent on the reaction kinetics of the whole system, as concluded by the chemical bond theory of single crystal growth [32][33][34]. The morphology and crystal phase of Cs x WO 3 synthesized by solvothermal reaction with different process parameters are summarized in Table 1.…”
Section: Effects Of Autoclave Rotating On the Morphology And Crystal supporting
confidence: 79%
“…The stretch of Zn O bonds on the {100}, (001) and (001) planes and the shrinkage of Zn O bonds on the {011} planes can generate the chemical bonding conditions to grow rod like ZnO nanostructures. 34 It is generally found that the concentration of OH − has a prominent effect on the growth behavior of ZnO. When the concentration of OH − is low in the solution, the growth along the c-axis is faster due to high surface energy.…”
Section: Resultsmentioning
confidence: 99%
“…2a showed that pure CdWO 4 exhibited uniform nanorod structure. The 0.5% Eu 3 þ :CdWO 4 prepared at different pH values were also nanorod structure, which indicated that low concentration doping of Eu 3 þ cannot change the morphology of CdWO 4 , particularly for its thermodynamic growth habit [31]. While the size distribution of these nanorods were different with the change of the pH values due to their kinetic control effect [32][33][34].…”
Section: Resultsmentioning
confidence: 99%